2008
DOI: 10.1021/es800626n
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Synthetic Musk Compounds in Mother′s Milk and Associations with Personal Use of Perfumed Products

Abstract: We analyzed two nitro musks (musk xylene and musk ketone) and five polycyclic musks (HHCB, AHTN, ADBI, ATII, and AHDI) in mother's milk from primiparae women (N = 101) living in Uppsala County, Sweden, 1996-2003. Possible temporal trends in musk concentrations and associations with lifestyle/medical factors, such as use of perfumed products during pregnancy were studied. HHCB showed the highest median concentration (63.9 ng/g lipid) followed by AHTN (10.4 ng/g) and musk xylene (MX) (9.5 ng/g). Concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 23 publications
(54 reference statements)
4
30
0
2
Order By: Relevance
“…Although concentrations of HHCB and AHTN were found to increase with age, no significant statistical relationship could be discerned according to regression analysis ( p > 0.05). The features were similar to those reported in human adipose and mother's milk [14]. However, the different age groups in female samples had a statistical significance with concentrations of HHCB according to Kruskal-Wallis test ( p < 0.05).…”
Section: Gender and Agesupporting
confidence: 83%
See 3 more Smart Citations
“…Although concentrations of HHCB and AHTN were found to increase with age, no significant statistical relationship could be discerned according to regression analysis ( p > 0.05). The features were similar to those reported in human adipose and mother's milk [14]. However, the different age groups in female samples had a statistical significance with concentrations of HHCB according to Kruskal-Wallis test ( p < 0.05).…”
Section: Gender and Agesupporting
confidence: 83%
“…In the present study, smoking was found not to be associated with synthetic musk compounds concentrations in human blood ( p > 0.05). Similarly, Lignell et al [14] also observed no association between smoking habits and musk concentrations in mother's milk; however, they reported a significant positive association between use of perfumed products and concentrations of HHCB and AHTN in mother's milk. Hutter et al [20] also indicated that persons using creams frequently showed high plasma concentrations of HHCB.…”
Section: Other Personal Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…Biocides are widely included in toothpaste, shampoo, and soaps with the functions of deterring, preventing the action of, or killing the harmful organisms [5]. Synthetic musks are used in a wide variety of cosmetics and perfumes [6]. Benzotriazoles are widely used as a corrosion inhibitor in cooling fluids, hydraulic fluids, and dishwasher detergents; an ultraviolet stabilizer in plastics; and an antifogging agent in photography and airplane defogging fluids [3].…”
Section: Introductionmentioning
confidence: 99%